Obesity Impact on Heart Rate Variability Indices and the Modulation Effect of Regular Physical Activity. - Hassan, Hayder S.; Almadfai, Zaid; Abdulkareem, Faris (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Obesity is imposing a growing threat to world health. The autonomic nervous system (ANS) regulates visceral functions via balance between sympathetic and parasympathetic divisions. In the cardiovascular system (CVS) this non stationary balance results in the fluctuation between intervals of consecutive heart beats, so called heart rate variability (HRV). Obesity is one of the causative co-morbid conditions leading to metabolic and cardiac disorders as it is accompanied with varied combinations of abnormalities in the ANS, one view is that obese people have higher sympathetic tone. HRV measures the effect of autonomic function on the heart alone. Therefore, it could be the most useful method to investigate the effect of obesity on CVS as obesity is associated with decreased HRV. Regular physical activity has been shown to increase HRV in healthy individuals. Therefore, exercise training may improve cardiac autonomic regulation in a variety of clinical populations including obese individuals. Objectives: to assess the alteration in cardiac autonomic function that may be associated with obesity by measuring HRV indices using (Holter monitoring) and to test the hypothesis that regular physical activity is associated with improved HRV. Methods: A total of 49 asymptomatic obese individuals (28 males, 21 females) were recruited from Obesity Unit in Alkindy College of Medicine/ University of Baghdad. Holter monitoring was applied to the obese individuals to assess HRV in addition to 47 healthy non-obese subjects of either sex as controls. All participants were subjected to 4-6 weeks moderate intensity of physical activity, and then Holter monitoring was repeated after the end of physical activity. Blood tests were done for all participants to exclude renal, liver and endocrine dysfunctions. Results: all HRV indices were significantly low in obese subjects (p value less than 0.05) body mass index (BMI) was negatively correlated with overall HRV index (p= 0.0001, r= - 0.87). After onset of regular physical activity, all HRV indices were increased significantly in obese subjects whereas the increase in HRV indices in normal weight subjects did not reach the level of significance. Conclusion: Obese subjects had a significant lower values of all HRV indices, overall low HRV values usually indicate a relative sympathetic dominance. BMI was negatively correlated with overall HRV index significantly in obese subjects. The significant increment in all HRV values in obese subjects after the onset of regular physical activity indicates a shift of sympathetic/parasympathetic balance towards increased vagal activity, which is a marker for cardiac autonomic modulation that may offset the negative effect of obesity.